Production economics and economic efficiency - Meireles, M. (Advanced mathematical methods for economic efficiency analysis: Theory and empirical applications, 2023)
This introductory chapter focuses on the different efficiency concepts, which are the base for the following chapters, highlighting their special importance. A particular emphasis is devoted to clarifying the main differences between the meanings of efficiency and effectiveness often confused and misunderstood. Exploring the main literature review on efficiency, this chapter addresses the significance and meaning of efficiency. Another concept often confused with efficiency is productivity, which is also clarified and analyzed. Based on the huge importance of assessing and improving the efficiency of producers, as well as comparing it between different producers, it also provides a review of efficiency and productive measures, such as the Malmquist and the Luenberger Productivity Indexes, as well as the DEA and SFA methodologies. In order to better explain the importance and applicability of the efficiency and productivity concepts and methodologies, this chapter also mentions some real-world applications of efficiency measures, for instance, on energy, environment, health, banking, education, and tourism.